Synthesis of Bi4Ti3O12/Alga for Ciprofloxacin Degradation - Prasetyo, Anton; Adi, Tri Kustono; Kartika, Siska Ela; Faturrohmi, Fauziah; Khanif, Juwita (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2025)
Antibiotic waste has become a serious issue for ecosystems, and one method that offers great potential to address this problem is photocatalysis. To enhance the photocatalytic activity, one approach is to impregnate the photocatalytic compound onto a supporting material and become composite material. In this study, Bi4Ti3O12/Algae (Spinossum cottonii, Euchema spinossum, and Sargassum sp) composite compounds were synthesized with various algae, including Sargassum and Spinosa. The diffractogram and IR spectra data indicate that the composite compounds were successfully synthesized. The photocatalytic activity test results demonstrate good potential for the Bi4Ti3O12/Euchema spinossum composite in the degradation of ciprofloxacin, as it was able to degrade 30% of ciprofloxacin within 60 minutes.